2017
DOI: 10.1371/journal.pone.0177306
|View full text |Cite
|
Sign up to set email alerts
|

Taking stock of the social determinants of health: A scoping review

Abstract: BackgroundIn recent decades, the social determinants of health (SDOH) has gained increasing prominence as a foundational concept for population and public health in academic literature and policy documents, internationally. However, alongside its widespread dissemination, and in light of multiple conceptual models, lists, and frameworks, some dilution and confusion is apparent. This scoping review represents an attempt to take stock of SDOH literature in the context of contemporary population and public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 71 publications
1
88
0
4
Order By: Relevance
“…Social determinants of health played an important role in addressing the sustainable development goals targets to promote health and well-being and to reduce disparity [ 3 ]. The social environment, comprising personal and societal relationships, institutions, cultures, and physical surroundings—all the aspects and products of human activity and interaction—is insufficiently researched in relation to health.…”
Section: Introductionmentioning
confidence: 99%
“…Social determinants of health played an important role in addressing the sustainable development goals targets to promote health and well-being and to reduce disparity [ 3 ]. The social environment, comprising personal and societal relationships, institutions, cultures, and physical surroundings—all the aspects and products of human activity and interaction—is insufficiently researched in relation to health.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also suggested a "social determination" approach, with an emphasis on the underlying social processes and structural forces that drive variations in the risk factors that affect health. 7 Greater recognition of the social determinants of health represents a welcome shift away from a focus on individual-level influences on health -which affords primacy to genetic and clinical factors -to a more complex viewpoint that includes societal, community and structural factors. 6 Consideration of these wider structural factors provides a much-needed opportunity to focus on the upstream causes of health variations (i.e., the causes of the causes), which supports preventing disease and enabling good health for all.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, a 2017 scoping review identified a paucity of publications on the social determinants of health from countries outside the Global North, thus limiting a global perspective and the application of the concept to the developing world. 7 Spiegel and colleagues 8 dissected the language of the social determinants of health, noting the dominance of a reductionist approach that focuses on risk factors related to individual living and working conditions or perhaps, at best, community influences, rather than bringing attention to structural and political processes, and…”
mentioning
confidence: 99%
“…In some cases, the impact of one or more interventions is at the core of the review [3][4][5][6][7], while in others it is the relationship between health and just one particular predictor, e.g., income inequality, access to healthcare, government mechanisms [8][9][10][11][12][13]. Some relatively recent reviews on the subject of social determinants of health [4][5][6][14][15][16][17] have considered a number of indicators potentially influencing health as opposed to a single one. One review defines "social determinants" as "the social, economic, and political conditions that influence the health of individuals and populations" [17] while another refers even more broadly to "the factors apart from medical care" [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some relatively recent reviews on the subject of social determinants of health [4][5][6][14][15][16][17] have considered a number of indicators potentially influencing health as opposed to a single one. One review defines "social determinants" as "the social, economic, and political conditions that influence the health of individuals and populations" [17] while another refers even more broadly to "the factors apart from medical care" [15].…”
Section: Introductionmentioning
confidence: 99%